HIV risk sexual behaviors among teachers in Uganda - Lillian Ayebale; Lynn Atuyambe; William Bazeyo; Erasmus Otolok Tanga (AOSIS, 2014)
Recent studies reveal that teachers are more likely to engage in high-risk sexual behavior compared to the rest of the adult population. Yet the education sector could be a major vehicle for imparting knowledge and skills of avoiding and/or coping with the pandemic. This study set out to establish HIV risk behaviors among teachers in Uganda, to inform the design of a behavior change communication strategy for HIV prevention among teachers. It was a cross sectional rapid assessment conducted among primary and secondary school teachers in Kampala and Kalangala districts, in Uganda. A total of 183 teachers were interviewed. HIV risk behavior, in this study was measured as having multiple sexual partners and/or sex with a partner of unknown status without using a condom. We also considered transactional/sex for favors and alcohol use as exposures to HIV risk behavior. Odds ratios (OR) and their corresponding 95% confidence intervals (CI) were calculated. All data analysis was performed using SPSS version 17.0 and EPI Info Version 3.5.1. Forty five per cent of teachers reported having multiple concurrent sexual partners in the last three months, of these, only 24% acknowledged having used a condom at their last sexual encounter yet only 9.8% knew their partners' HIV status. Teachers below 30years of age were more likely to have two or more concurrent sexual partners (OR 2.6, CI 1.31-5.34) compared to those above 30 years. Primary school teachers were less likely to involve with partners of unknown HIV status compared to secondary school teachers (OR 0.43, CI 0.19-0.97). Teachers aged below 30 years were also more likely to engage with partners of unknown HIV status compared to those above 30 years (OR 2.47, CI 1.10-5.59). Primary teachers were also less likely to have given or received gifts, money or other favors in exchange for sex (OR 0.24, CI 0.09-0.58). Teachers engage in risky sexual behaviors, which lead to HIV infection. There is need to promote individual risk perception, condom use and reduction in sexual partners. Also to encourage partners to know each other's status, and teachers to avoid risky situations or carefully negotiate such situations.